2019
DOI: 10.3390/cancers11081111
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of miR-20a as a Diagnostic and Prognostic Biomarker for Colorectal Cancer: A Systematic Review and Meta-Analysis

Abstract: Background: MicroRNAs have altered expression levels in various diseases and may play an important role in the diagnosis and prognosis of colorectal cancer (CRC). Methods: We systemically reviewed and quantitatively synthesized the scientific evidence pertaining to microRNA-20a (miR-20a) as a CRC biomarker. A keyword and reference search in PubMed yielded 32 studies, in which miR-20a was measured in feces, serum, or tumor tissue. Data were extracted from a total of 5014 cancer cases and 2863 controls. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 79 publications
(214 reference statements)
1
24
1
1
Order By: Relevance
“…Most of the studies reported that this miRNA has a low expression in cancer patients than in the controls. This finding is in line with other studies analyzing the role of other miRNAs in colorectal cancer [ 44 , 45 ]. In a recent meta-analysis, low expression of miR-143 and miR-145 is correlated with a poor survival prognosis [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…Most of the studies reported that this miRNA has a low expression in cancer patients than in the controls. This finding is in line with other studies analyzing the role of other miRNAs in colorectal cancer [ 44 , 45 ]. In a recent meta-analysis, low expression of miR-143 and miR-145 is correlated with a poor survival prognosis [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…For example, lncRNA GHET1 is overexpressed in various cancers, which can predict unfavorable survival and clinical parameters in patients (73). Recent literature has shown that miR-20a is overexpressed in colon cancer and acts as a diagnostic and prognostic biomarker (74). lncRNAs and miRNAs can also be combined for the diagnosis of cancer.…”
Section: Lncrnas and Mirnas In Cancermentioning
confidence: 99%
“…In recent years, high-throughput biotechnology is widely used to identify genes marker for CRC. [18][19][20] It suggested that a deeper understanding of the genetic characteristics of CRC may lead to a better risk stratification system. Furthermore, many studies have explored the role of autophagy mechanisms in tumorigenesis, including CRC.…”
Section: Discussionmentioning
confidence: 99%